2008
DOI: 10.1016/j.ssi.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of LiFePO4/C composite obtained by sonochemical method

Abstract: Lithium iron phosphate has become of great interest as storage cathode for the next generation of rechargeable lithium batteries. Olivine structure LiFePO 4 /C composite powder was prepared by ultrasound assisted synthesis. A polyvinyl alcohol solution was used as the source of an in situ formed carbon. X-ray powder diffraction confirmed the phase purity. X-ray powder diffraction data were used for the crystal structure refinement, based on Rietveld full profile method. All relevant structural and microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 18 publications
(21 reference statements)
0
26
0
Order By: Relevance
“…918 synthesis process [8], microwave-solvothermal synthesis method [9], sol-gel synthesis technique [10], spray pyrolysis technique [11], co-precipitation technique [12], carbothermal reduction technique [13] and many more techniques [14].…”
mentioning
confidence: 99%
“…918 synthesis process [8], microwave-solvothermal synthesis method [9], sol-gel synthesis technique [10], spray pyrolysis technique [11], co-precipitation technique [12], carbothermal reduction technique [13] and many more techniques [14].…”
mentioning
confidence: 99%
“…The use of lithium ion batteries in large-scale commercial applications is avoided since the oxygen release at higher temperatures can cause explosion [5]. A number of attempts were made to overcome these limitations [6][7][8]. Electron transport of these materials was enhanced by applying conducting layer around LiFePO 4 , which includes silver [8], carbon-based materials [6,7], conducting polymers [9][10][11], and doping of LiFePO 4 using foreign conducting materials [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A number of attempts were made to overcome these limitations [6][7][8]. Electron transport of these materials was enhanced by applying conducting layer around LiFePO 4 , which includes silver [8], carbon-based materials [6,7], conducting polymers [9][10][11], and doping of LiFePO 4 using foreign conducting materials [9,10]. Secondly, the improvement in capability of LiFePO 4 materials was carried out by increasing the surface area by reducing the particle size and use of a uniform narrow particle size distribution [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Yi et al [32] reported that LiAl 0.05 Mn 1.95 O 4 powder with uniform, nearly cubic structure and octahedral morphology with narrow size distribution can be obtained by the ultrasonic-assisted sol-gel method. With this advantage, Jugovic et al [33] reported that LiFePO 4 /C composite powder was prepared using a sono-chemical reaction by the application of powerful ultrasound radiation (20 kHz). However, this material exhibited a lower discharge capacity (94 and 124 mAh g −1 at C/3 and C/10, respectively) due to the dislocation of iron ions on lithium sites (3%), which could block the whole channel and prevent lithium motion.…”
Section: Introductionmentioning
confidence: 99%